2008
DOI: 10.1055/s-0038-1625529
|View full text |Cite
|
Sign up to set email alerts
|

Estudo de traumatismo craniencefálico experimental em ratos com aparelho de impacto cortical controlado

Abstract: Resumo Objetivo: Desenvolver um modelo de impacto cortical controlado (pneumático) para traumatismo craniencefálico experimental em ratos, sem exposição do encéfalo. Métodos: Com base em relatos da literatura, foi construído um modelo de impacto cortical pneumático, sendo testado em 30 ratos, com análise histopatológica de todos os animais. Resultados: Os resultados da análise histopatológica baseada na contagem de neurônios lesados por campo demonstraram a eficiência do modelo na produção de lesão t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…The histopathologycal findings described in this study are close of those observed in others researches involving closed head trauma in rats produced by others types of devices such as those operated by pneumatic pressure 10 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The histopathologycal findings described in this study are close of those observed in others researches involving closed head trauma in rats produced by others types of devices such as those operated by pneumatic pressure 10 .…”
Section: Discussionsupporting
confidence: 90%
“…Many experimental models were performed in the last decades so as to reproduce head trauma in laboratory [1][2][3] .A group of these studies uses the weight drop right trauma model mechanism or produces encephalic lesions through using pneumatic pistons regulated by compressed air 10 . The head trauma experimental models intend to reproduce the complex physiopathology of traumatic brain injury in laboratory in order to allow the development of new therapeutic approaches 1,2 .…”
Section: Discussionmentioning
confidence: 99%
“…Traumatic brain injury has a complex pathophysiology and happens in phases with several space and time specific mechanisms 1,2 . Many experimental studies 2 Several related models in the literature [2][3][4] allow producing a varied range of lesions from simple and reproducible mechanic principles, such as the models of weight dropping and direct impact by pneumatic piston. These models are able to produce a controlled cortical impact with increasing energy levels 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Many experimental studies 2 Several related models in the literature [2][3][4] allow producing a varied range of lesions from simple and reproducible mechanic principles, such as the models of weight dropping and direct impact by pneumatic piston. These models are able to produce a controlled cortical impact with increasing energy levels 4 . The model involving weight fall has been used for a long time in order to produce diffuse lesions on encephala of rats for researches on experimental traumatic brain injury 2,3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation